2011
DOI: 10.2135/cropsci2010.04.0217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and 6‐Benzylaminopurine on Rice Tiller Bud Growth and Changes in Endogenous Hormones and Nitrogen

Abstract: In the present study, 40 mg L−1 N (NH treatment) and 20 mg L−1 6‐benzylaminopurine (6‐BA; BA treatment) were used to stimulate tiller bud growth in rice (Oryza sativa L.). The hormone changes in the tiller nodes and tiller buds and the N levels in the leaf blades, leaf sheaths, and tiller nodes were measured. The results indicate that N and 6‐BA promoted tiller bud germination and increased the indole‐3‐acetic acid (IAA) and zeatin (Z) plus zeatin riboside (ZR) levels in tiller buds and tiller nodes but decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 31 publications
4
44
0
2
Order By: Relevance
“…1). Our previous study showed that N might regulate tiller bud growth through at least two mechanisms: by regulating N metabolism and endogenous hormone levels (Liu et al 2011c). We focused on the hormone pathway in the present study and found that N could significantly promote the amounts of all forms of endogenous CKs in both tiller buds and nodes (Table 1).…”
Section: Discussionmentioning
confidence: 58%
“…1). Our previous study showed that N might regulate tiller bud growth through at least two mechanisms: by regulating N metabolism and endogenous hormone levels (Liu et al 2011c). We focused on the hormone pathway in the present study and found that N could significantly promote the amounts of all forms of endogenous CKs in both tiller buds and nodes (Table 1).…”
Section: Discussionmentioning
confidence: 58%
“…For instance, N is a critical component of all amino acids, whereas P is a critical component of adenosine triphosphate (ATP). Besides, it has been reported that N fertilizers can directly affect the phytohormones, so that plants fertilized with N had significantly higher level of indole-3-acetic acid (IAA) and gibberellins compared to N-starved plants (Liu et al, 2011;Wiser, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Through polar transport, IAA can regulate the synthesis of CTK; in this way, it is able to regulate the growth of lateral buds (Wang et al, 2006). The basal internodes of rice are not elongated, and this structural characteristic may lead to a deficiency in polar transport of IAA in the aboveground organs (Liu et al, 2011). In the tillering stage, the fifth bud was located at the leaf axils of the fifth leaf from the bottom on the main stem.…”
Section: Discussionmentioning
confidence: 99%